Long-Term Labor Force Exit and Economic Well-Being: A Cross-National Comparison of Public and Private Income Support - Richard V. Burkhauser; Dean R. Lillard; Paola M. Valenti (Vierteljahrshefte zur Wirtschaftsforschung, 2001)
This paper examines how the economic well-being of households changes after a male household member exits the labor force. We examine, in four countries, labor force exits at various ages and present evidence on household income from various sources before and after the exit occurs. We focus on the rate at which household income is replaced through public and private means after labor force exit. We find that economic well-being is underestimated when researchers follow the traditional focus in this literature and consider replacement of earnings through public pension programs. When one measures total household income, after taxes and transfers, before and after labor force exits, not only is economic well-being greater but cross-country differences are reduced.
Keywords: 330; Altersvorsorge; Haushaltseinkommen; Ältere Arbeitskräfte; Männer; Altersgrenze; Private Altersvorsorge; Vergleich; USA; Deutschland; Großbritannien; Kanada